Some quick arithmetic - Mildner, Vesna (2001)
Mathematical abilities for the four simple arithmetic operations were studied on a sample of 53 female right-handers. True and false statements were presented auditorily and a manual response was required as to the trueness of the statements. Response times, accuracy, and laterality index showed no significant ear advantage, but the responses to true statements were significantly faster than to the false ones. The shortest response times were found for addition problems, and the longest for subtractions. The correlation between the size of the difference between the two operands and response time was not conclusive but the trend was unexpectedly positive.
Projekt MZOS
ENG